Case report: A novel PPP3CA truncating mutation within the regulatory domain causes severe developmental and epileptic encephalopathy in a Chinese patient - Li, Jieling; Cao, Jie (Frontiers in Neurology, 2022)
Introduction Developmental and epileptic encephalopathy 91 (DEE91; OMIM#617711) is a severe neurodevelopmental disorder caused by heterozygous PPP3CA variants. To the best of our knowledge, only a few DEE91 cases have been reported. Results This study reports a boy who experienced recurrent afebrile convulsions and spasms at the age of 2 months. After being given multiple antiepileptic treatments with levetiracetam, adrenocorticotropic hormone (ACTH), prednisone, topiramate, and clonazepam, his seizures were not completely relieved. At the age of 4 months, the patient exhibited delayed neuromotor development and difficulty in feeding; at the age of 6 months, he was diagnosed with developmental regression with recurrent spasms and myoclonic seizures that could respond to vigabatrin. At the age of 1 year and 4 months, the patient showed profound global developmental delay (GDD) with intermittent absence seizures. Whole-exome sequencing (WES) identified a novel loss-of-function variant c.1258_1259insAGTG (p. Val420Glufs*32) in PPP3CA. Conclusion This finding expands the genetic spectrum of the PPP3CA gene and reinforces the theory that DEE91-associated truncating variants cluster within a 26-amino acid region in the regulatory domain (RD) of PPP3CA.